A novel coordination mode for pentalene in trinuclear chromium complexes. - Jones, S; Hascall, T; Norquist, A; O'Hare, D (2003)
The first chromium pentalene complexes have been characterized; in these the ligand displays a hitherto-unknown bonding mode whereby a dimeric [Cr(Cp*)](2)(mu-OR) unit is bound (mu:eta(2):eta(2))- to one face, and Cp*Cr is bound eta(5)- to the other. The magnetic properties of these compounds can be understood as the superposition of those of a chromocene and an antiferromagnetically coupled Cr[bond]Cr bonded unit.